Long-term recovery from acute cold shock in Caenorhabditis elegans. Issue 1 (December 2016) - Robinson, Joseph; Powell, Jennifer
Abstract Background Animals are exposed to a wide range of environmental stresses that can cause potentially fatal cellular damage. The ability to survive the period of stress as well as to repair any damage incurred is essential for fitness. Exposure to 2 °C for 24 h or longer is rapidly fatal to the nematodeCaenorhabditis elegans, but the process of recovery from a shorter, initially non-lethal, cold shock is poorly understood. Results We report that cold shock of less than 12-hour duration does not initially killC. elegans, but these worms experience a progression of devastating phenotypes over the next 96 h that correlate with their eventual fate: successful recovery from the cold shock and survival, or failure to recover and death. Cold-shocked worms experience a marked loss of pigmentation, decrease in the size of their intestine and gonads, and disruption to the vulva. Those worms who will successfully recover from the cold shock regain their pigmentation and much of the integrity of their intestine and gonads. Those who will die do so with a distinct phenotype from worms dying during or immediately following cold shock, suggesting independent mechanisms. Worms lacking the G-protein coupled receptor FSHR-1 are resistant to acute death from longer cold shocks, and are more successful in their recovery from shorter sub-lethal cold shocks. Conclusions We have defined two distinct phases of death associated with cold shock and described a progression of phenotypes that accompanies the course of recovery from that cold shock. The G-protein coupled receptor FSHR-1 antagonizes these novel processes of damage and recovery.